Time Management Skills of Sixth Literary Students Upon Their View Point - Al-Hamadani, Mohammed Kadhim Mantoob; Kadhim, Raad Talib (International Journal of Psychosocial Rehabilitation, 2020)
The scientific and civilizational progress that we have touched on various aspects of our contemporary life has become a reality embodied in the reality of our human societies due to its ability and skill to plan well the available time to it and make the best use of it, so it has become an urgent need to adopt scientific and technological systems as a necessity of the continuation of life, so our schools were obligated Keeping pace with scientific developments; to achieve educational outcomes with more efficiency and more effectiveness to alleviate educational problems, which are effective in developing time management skills, The importance of research can be explained in the following points: • Explain the students ’role in maintaining, managing and investing time • The importance of this research stems from the novelty of its topic as it represents a real response to one of the most prominent issues and challenges facing our schools. So the aim of the current research is to identify the time-management skills of sixth-graders of literary students from their point of view, and it was limited to sixth-graders of literary students in Al-Qadisiyah governorate schools for the academic year (2018-2019). To achieve the goal of the research, the two researchers used the descriptive approach and building a scale of time management skills. The research sample consisted of 400 students from the original community who were randomly selected. As for the research tool, a time management skills scale consisting of (20) items, and its validity and reliability were confirmed. The two researchers statistically processed the data to extract the results using the Pearson correlation coefficient and the t-test for one sample, and the results showed that time management skills among sixth literary students were good and they had poor planning skill, and in light of the results the researchers developed a number of conclusions, recommendations and suggestions.